Efektifitas Permainan Word Search dengan Pendekatan Self-Paced Learning dalam Pembelajaran Mufrodat di Madrasah Tsanawiyah Darul Falah Tulungagung - Hima Roiku Dinia; M. Abdul Hamid; Nur Hasan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The Word Search vocabulary game method involves searching for words within a randomly arranged grid of letters, which can be organized both horizontally and vertically. This method is implemented using a self-paced learning approach, providing students with the flexibility to learn independently and manage their time, pace, and learning path according to their needs. The aim of this research are to determine the effectiveness of the Word Search game with a self-paced learning approach in vocabulary learning at Madrasah Tsanawiyah Darul Falah Tulungagung. This study is a quasi-experimental study with a purposive sampling method. The subjects of this study were eighth grade students at Madrasah Tsanawiyah Darul Falah Tulungagung, with a total of 60 students. Data collection methods include observation and tests. Data analysis used the t-test with the SPSS 27 program. The results of this study are the hypothesis test results show a significance value of 0.001 < 0.05, indicating a significant effect of the Word Search game on vocabulary learning at Madrasah Tsanawiyah Darul Falah Tulungagung. In terms of the effectiveness of the Word Search game with a self-paced learning approach, the N-gain results reached 70.2%, which, according to the gain interpretation, indicates that it is quite effective.